The Efficacy of Reamberin in Correction of Lipoperoxidation Processes in the Gastrointestinal Form of Salmonellosis - V. F. Pavelkina; YU. G. Uskova (Антибиотики и Химиотерапия, 2020)
The purpose of the study was to evaluate the dynamics of the peroxidative homeostasis processes (lipid peroxidation and antioxidant protection) in the moderate gastrointestinal form of salmonellosis during complex therapy including reamberin. Seventy patients with moderate salmonellosis were examined: 35 patients of the control group received basic therapy, 35 patients of the main group received reamberin (intravenously, 1.5% - 500 ml per day, for 5 days) in addition to the basic therapy. The efficacy of therapy was assessed according to the dynamics of clinical symptoms relief and laboratory data: the level of diene conjugates (DCo), diene ketones (DKe), plasma and erythrocytes malonic dialdehyde (MDApl, MDAer), plasma and erythrocyte catalase (Cpl, Cer) and superoxide dismutase (SOD). It is established that an imbalance in the prooxidant and antioxidant system remains in the phase of clinical recovery from salmonellosis. The inclusion of reamberin in the complex pathogenetic therapy made it possible to more effectively cope with the clinical symptoms of the disease and the parameters of peroxide homeostasis, as evidenced by a decrease in lipid peroxidation products (DCo, DCe, MDApl, MDAer) and an increase in the activity of antioxidant enzymes (Cpl, Cer, SOD). The inclusion of reamberin in the treatment of patients with salmonellosis should be considered pathogenetically and clinically justified and promising.